Buffer-based dynamic provisioning for sliding bulk transfer requests in WDM optical networks - Zhong, Wende (2013)
We present a new model for dynamically provisioning sliding bulk transfer requests in data-intensive applications over wavelength-division multiplexing (WDM) optical networks. This model can provide more flexibility for the users and serve them better. It allows the users not only to specify the sizes of submitted bulk files, but also to make decisions on the minimum bandwidth guarantee (MBG) and the time redundancy (TR) of the sliding window. We formulate the problem into two sub-problems (time scheduling, routing-wavelength assignment (RWA) and bandwidth allocation (BA)) and prove it to be NP-complete. We propose a buffer-based provisioning (B2P) architecture to deal with the problem. The approach first temporarily buffers those blocked requests at their arrival times and then attempt to provision these requests later once new resources become available. The effectiveness and the feasibility of the proposed approach are demonstrated by the simulations.